Fertilization and Irrigation Technology in a Double-Row (76×10 cm) Scheme Based on New Intensive Agrotechnology under the Conditions of Samarkand Region - Quchqarovich , Diyarov G‘olibjon; Qurbonboy o‘g‘li , Otaqulov Azamatjon; Raximjon o‘g‘li , Elomonov Javohir (American Journal of Biology and Natural Sciences, 2026)
At the Samarkand Scientific Experimental Station, in 2025, Xin Lu Zao-78 cotton variety was planted in double rows under the film with a row spacing of 76x10 based on foreign technology. Stom-P Original 33% k.e. containing 330 g/l of pendimethalin was sprayed against weeds. Before sowing, 80-100 percent of the annual rate of phosphorus fertilizers (250-300 kg/ha in physical form of ammophos) and 80-100 percent of potassium fertilizers (100-120 kg/ha of potassium chloride) were applied under the chisel-harrow. Water-soluble NPK fertilizers were applied in solution through drip irrigation according to the recommendations. During the season, irrigation was carried out at a rate of 930-1155 m³/ha.